2021
DOI: 10.1007/s10461-021-03384-9
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Randomized Controlled Trial of Motivational Interviewing with Sexual Minority Male Couples to Reduce Drug Use and Sexual Risk: The Couples Health Project

Abstract: A randomized controlled trial evaluated the preliminary efficacy of a dyadically-delivered motivational interviewing (MI) intervention to reduce drug use and sexual risk in a sample of 50 sexual minority (cis)male (SMM) couples. In each couple, at least one partner was aged 18-29; reported drug use and sexual HIV transmission risk; and was HIV-negative. Couples were randomized to either the three-session MI intervention or an attention-matched control, with follow-up surveys completed at 3-and 6-months post-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…It can be concluded that motivation for treatment is integral to drug management [18]. Motivational interviewing techniques were considered appropriate for aversive drug use of any intensity , different age groups and settings [19]. Moreover addictive persons were also found with dysfunctional attitudes [20].…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that motivation for treatment is integral to drug management [18]. Motivational interviewing techniques were considered appropriate for aversive drug use of any intensity , different age groups and settings [19]. Moreover addictive persons were also found with dysfunctional attitudes [20].…”
Section: Resultsmentioning
confidence: 99%
“…For several decades, scholars have noted the limited scope of individual-level HIV prevention and care interventions and called for research that focuses on the relational contexts that contribute to HIV transmission risk and promote optimal HIV care continua outcomes [40,41]. The field has seen the development and evaluation of couples-based interventions focused on HIV prevention and treatment [42], with two published within the past year [43,44]. Additionally, a third study evaluated a dyadic-level intervention with friendship pairs to increase HIV testing among young Black sexual minority men and transgender women [45 & ].…”
Section: Dyadic-level Interventionsmentioning
confidence: 99%
“…There are already examples of empirically supported dyadic interventions intended to improve relationship functioning (e.g., Strengthening Same-Sex Relationships; Whitton et al, 2017). Further, behavioral health interventions that seek to reduce substance use or sexual risk taking in part by improving dyadic functioning have been developed for at least some SGM subgroups (e.g., Newcomb et al, 2020; Starks et al, 2021). While this work has been valuable, these interventions have not typically been conceived as enhancing couples’ capacity to cope with minority stress specifically.…”
Section: Recommendations For Clinical Practicementioning
confidence: 99%